2017
DOI: 10.26773/mjssm.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Swim Speed Tests as a Method for Differentiating the Profiles of Young Swimmers

Abstract: Swimming tests are used in every training cycle and seasons with purpose of estimating swimming performance and evaluate certain training types. Th e focus of this study is an attempt to distinguish between the potential short-distance and longer-distance swimmers, as well as the swimmers who could have desirable profi les for particular swimming styles. For this purpose, several aims are given: () to determine the latent dimensions of the performances in swimming tests, conducted on various distances and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
1
5
0
1
Order By: Relevance
“…The backstroke, breaststroke, and front crawl velocities we recorded in our study participants were similar to those reported for similar-age girls by other authors [37][38][39]. It has been shown that, regardless of the swimming distance, the front crawl is associated with the highest velocity, while the breaststroke is the slowest, probably because frontal water resistance in breaststroke is greater than in other styles [36,40]. The results of our study are consistent with this finding.…”
Section: Discussionsupporting
confidence: 92%
“…The backstroke, breaststroke, and front crawl velocities we recorded in our study participants were similar to those reported for similar-age girls by other authors [37][38][39]. It has been shown that, regardless of the swimming distance, the front crawl is associated with the highest velocity, while the breaststroke is the slowest, probably because frontal water resistance in breaststroke is greater than in other styles [36,40]. The results of our study are consistent with this finding.…”
Section: Discussionsupporting
confidence: 92%
“…In the fi eld of sport research and sociopsychology, MJSSM's activities include: "Preliminary psychometric validation of the Multidimensional inventory of sport excellence: attention scales and mental energy" (Sindik, Botica, & Fiskus, 2015), "Socioeconomic, Personal and Behavioral Correlates of Active Commuting among Adolescents" (Marques, Peralta, Sarmento, Martins, & Carreiro da Costa, 2016), "Th e Impact of Social Capital Domains on Self-Rated Health among Serbian High School Students?" (Novak et al, 2016), "Health-Related Fitness Knowledge of Middle School Students in Public and Private Schools" (Serbes, Cengiz, Sivri, & Filiz, 2017), "Comparison of Standard and Newer Balance Tests in Recreational Alpine Skiers and Ski News" (Cigrovski, Franjo, Rupcic, Bakovic, & Matkovic, 2017), "Systemic Mapping of High-Level Women's Volleyball Using Social Network Analysis: Th e Case of Attack Survey, Freeball and Downball" (Hurst et al, 2017), "Medical Students Awareness of the Connections between Physical Activity and Health" (Mandic, Wilson, Clark-Grill, & O'Neill, 2017), "Swim Speed Tests as a Method for Diff erentiating the Profi les of Young Swimmers" (Siljeg, Sindik, & Leko, 2017 ), "Examining Attitudes of Physical Education Teacher Education Program for Students in Teaching Profession" (Yildizer, Ozboke, Tascioglu, & Yilmaz, 2017), "A Comprehensive Mapping of High-Level Men's Volleyball Gameplay Th rough Social Network Analysis: Analyzing Serve, Side-Out, Side Transformation and Transition" (Loureiro et al, 2017), "Collaborative Learning with the Application of Screen-Based Technology in Physical Education" (Luptáková & Antala, 2017), "Functional-Strengthening: A Pilot Study on Balance Control Improvement in Community-Dwelling Older Adults" (Josephson & Williams, 2017), "Perceived Autonomy Support and Basic Psychological Needs of Participants in a Women's Health-Related Exercise Program according to Exercise Stage of Change and Exercise Type" (Mehrtash & Ince, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Even though it is indexed into the "Web of Science" database, this journal still does not have a certain impact factor, since it is in the "Emerging Source Citation Index", and the next step that this journal is expected to achieve is that the " Web of Science "database assigns an impact factor and to be included in one of the remaining three bases (SCI, SSCI or SCIE). To reach that goal, the number of articles in each edition has increased, so in the fi rst (Marques, Peralta, Sarmento, Martins, & Carreiro da Costa, 2016;Sarabon, Hirsch, & Majcen, 2016;Saether, 2016;Silva, Marcelino, Lacerda, & Vicente João, 2016;Sindik, Mikic, Dodigovic, & Corak, 2016) or the second issue of the fi ft h volume (Arazi, Asadi, & Chegini, 2016;Novak, Milanovic, Radisavljevic Janic, Stefan, & Kristicevic, 2016, Oliveira, Valladares, Vaz, & João, 2016Roga, Erceg, & Grgantov, 2016;Stojanovic et al, 2016) fi ve articles replaced with ten in the fi rst (Bülent Okan, 2017;Cigrovski, Franjo, Rupcic, & Bakovic, 2017;Hurst et al, 2017;Jelicic, Uljevic, & Zenic, 2017;Morteza Tayebi, Mahmoudi, Shirazi, & Sangi, 2017;Gardasevic, Rasidagic, Krivokapic, Corluka, & Bjelica, 2017;Popovic, 2017;Serbes, Cengiz, Sivri, & Filiz, 2017;Sindik et al, 2017), and the second issue of the sixth volume (Josephson, & Williams, 2017;Kozinc, & Sharabon, 2017;Loureiro et al, 2017;Luptáková, & Antala, 2017;Mandic, Wilson, Clark-Grill, & O'Neill, 2017;Nepocatych, Balillions, & O'Neal, 2017;Saether, 2017;Siljeg, Sindik, & Leko, 2017;Valleser, & Narvasa, 2017;Yildizer, Ozboke, Tascioglu, & Yilmaz, 2017), and continued with the practice of publishing twenty art...…”
Section: Discussionmentioning
confidence: 99%